An RTSP Proxy for Implementing the IPTV Media Function Using a Streaming Server - Shibeshi, Z.S.; Terzoli, A.; Bradshaw, K. (Informatica)
An RTSP Proxy for Implementing the IPTV Media Function Using a Streaming Server